Integrasi Aplikasi Let’s Read dalam Model RADEC untuk Meningkatkan Kemampuan Membaca Pemahaman Di Sekolah Dasar - Feby Inggriyani (Universitas Pahlawan Tuanku Tambusai, 2026)
Reading comprehension remains a challenge in primary school education. Teacher-centered instructional methods, limited use of digital learning resources, and a lack of diversity in reading materials can hinder student engagement with texts. This study examines the implementation of the